Monetary Policy and Financial Stability in the Long Run - Jin Cao; Lorań Chollete (Norges Bank, 2013)
Most theoretical central bank models use short horizons and focus on a single tradeoff. However, in reality, central banks play complex, long-horizon games and face more than one tradeoff. We account for these issues in a simple infinite-horizon game with a novel tradeoff: higher rates deter financial imbalances, but lower rates reduce the likelihood of insolvency. We term these factors discipline and stability effects, respectively. The central bank's welfare decreases with dependence between real and financial shocks, so it may reduce costs with correlation-indexed securities. In our model, independent central banks cannot in general attain both low inflation and financial stability.
hdl:11250/2496684
Keywords: E50; G21; G28; 330; central bank; correlation-indexed security; discipline effect; stability effect